Democratic administration for good governance : a felicitation volume in honour of Professor (Dr.) R.D. Sharma on his 75th birthday - Hazarika, Niru (New Delhi : Kanishka Publishers, Distributors, 2012)
Dr. R.D. Sharma, born 1937, former Professor of Public Administration in the Institute of Policy Research and Analysis; contributed articles.
Includes bibliographical references and index.
Keywords: DEMOCRACY -- INDIA; DECENTRALIZATION IN GOVERNMENT -- INDIA; PUBLIC ADMINISTRATION -- INDIA